2019
DOI: 10.1016/j.neubiorev.2019.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal difficulties in obesity: A systematic review and meta-analysis to inform a rejection sensitivity-based model

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 73 publications
2
29
1
Order By: Relevance
“…Heterosexual men with MO seek to improve their health (Barragán et al., 2018), body image and sexual function (Rowland et al., 2016); failure to lose weight (Sharman et al., 2016) and aesthetic reasons (Bertoletti et al., 2019) explain their commitment to bariatric surgery (Quinn‐Nilas et al, 2016); and as these beliefs may be unrealistic, they can generate frustration (Homer, Tod, Thomson, Allmark, & Goyder, 2016). Inspired by Merleau‐Ponty’s notion of consciousness as embodied, participants confirm that MO may be related to loneliness, stigma and social isolation (Albano et al., 2019; Nath, 2019), moving towards self‐pity (Ramos et al., 2019).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Heterosexual men with MO seek to improve their health (Barragán et al., 2018), body image and sexual function (Rowland et al., 2016); failure to lose weight (Sharman et al., 2016) and aesthetic reasons (Bertoletti et al., 2019) explain their commitment to bariatric surgery (Quinn‐Nilas et al, 2016); and as these beliefs may be unrealistic, they can generate frustration (Homer, Tod, Thomson, Allmark, & Goyder, 2016). Inspired by Merleau‐Ponty’s notion of consciousness as embodied, participants confirm that MO may be related to loneliness, stigma and social isolation (Albano et al., 2019; Nath, 2019), moving towards self‐pity (Ramos et al., 2019).…”
Section: Discussionmentioning
confidence: 89%
“…Morbid obesity has been linked to depression, anxiety, low self‐esteem (Taskin, Karakoc, & Demirel, 2019) and body image disorders (Nath, 2019). Furthermore, MO can negatively affect individuals' social relationships (Albano, Rowlands, Baciadonna, Lo Coco, & Cardi, 2019) and sexual health (Rowland et al., 2016; Sfahani & Pal, 2019). Sexuality is a central aspect of human life and includes sex, gender role, sexual orientation, eroticism, pleasure or reproduction and is influenced by biological, psychological, social and cultural factors (WHO, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Social anxiety, poor social support, and interpersonal difficulties were reported also in patients with bulimia nervosa (BN; [ 41 , 48 ]), who also showed reduced performances on the RMET compared to controls [ 47 ]. People with binge-eating disorder (BED) or with eating disorder not otherwise specified (EDNOS) were less often investigated on their performances on the RMET [ 49 , 50 ], although both people with BED [ 51 ], and EDNOS [ 52 ], experience interpersonal difficulties. Moreover, BED and EDNOS displaying disordered eating with binge eating may evolve into obesity [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using the Cyberball task to evaluate patients with obesity have demonstrated the possible roles of shame and social isolation in developing and maintaining an over-eating behavior by showing an increase in food intake after being ostracized [ 30 ] as well as the rise of the perceived shame [ 42 ]. A recent meta-analysis has shown that people with obesity report higher interpersonal adversity, higher perceived interpersonal stress, and a lower quality of social life; these findings illustrate the need for psychological interventions targeted toward interpersonal sensitivity [ 2 ]. However, nothing is known about the responses of obesity surgery patients at the Cyberball task.…”
Section: Introductionmentioning
confidence: 99%